A computerized tool for the kinematic limit analysis of 2D masonry structures failing on a tilting table - Yiwei Hua; Martina Buzzetti; Natalia Pingaro; Luis C.M. da Silva; Gabriele Milani (SoftwareX)
A Limit Analysis computer Code for masonry walls collapsing in Tilting Table Tests (LACT3) is presented. Specifically, LACT3 is a MATLAB®-based graphical user interface useful to determine the ultimate load-bearing capacity of masonry walls in-plane loaded. The latter are modelled within a heterogeneous approach where blocks are assumed infinitely resistant and joints are reduced to interfaces exhibiting an associated rigid-plastic behaviour, ruled by a Mohr-Coulomb failure criterion. At incipient collapse, the mechanical problem can be therefore described by means of the two classic limit analysis theorems. LACT3 extracts the geometry of the masonry wall directly from a dxf file, with a precise description of block dimension and shape. The upper bound theorem of limit analysis is used, and the collapse tilting angle is determined along with the corresponding failure mechanism, recursively solving a linear programming problem at progressively increased values of rotation of the tilting table. Additionally, the self-dual linear programming approach enables the evaluation of internal actions. The proposed tool is highly user-friendly, requiring only a basic knowledge of CAD software, and is easily manageable as it requires only two mechanical parameters for the joints: (i) friction angle and (ii) cohesion. LACT3 provides an efficient means for the rapid assessment of 2D masonry structures under horizontal loads.